ADAPTING EUROPEAN MODELS OF PUBLIC ADMINISTRATION TO THE CONDITIONS OF POST-WAR UKRAINE: CHALLENGES AND PROSPECTS - Karsim, Andrii (Public Management and Policy, 2025)
The article addresses adapting European public administration models to Ukraine’s post-war circumstances. Numerous strategic, political, and practical elements have contributed to the development of a new state administrative model in Ukraine, aimed at ensuring an efficient recovery following the war and fostering progress towards EU integration. Adapting European public administration models to post-war Ukraine’s situation will strengthen the European integration pathway, align public administration standards with European demands, and establish a contemporary, open, and efficient state. The study’s objective is to examine essential European public administration models and evaluate their applicability for implementation within the Ukrainian post-war setting. The main focus is on European governance models’ analysis, seeking equilibrium between international governance benchmarks and national traits, considering war-related and national issues. The research employs techniques like comparative and analytical approaches, systematic methods, institutional analysis, and predictive methods. The alteration of public administration systems during crises and wars is probed. European public administration models and the experiences of other Central and Eastern European nations that have undergone post-conflict reconstruction are scrutinized to find effective practices applicable in Ukraine. The state and difficulties of public administration in Ukraine in the post-war period are assessed. Opportunities for adapting European models in Ukraine are identified. The part of international aid and European integration is determined. Scientifically valid guidance on the effective adaptation of European models of public administration in the setting of post-war advancement of Ukraine is formulated. Future research in the area of adaptation of European models of public administration to the circumstances of post-war Ukraine should aim at improving management tools and considering the changing challenges of post-war recovery, which will aid the development of an effective, sustainable, and European-focused governance system in Ukraine.